The pattern of reported adverse drug reactions with reference to specific drug class and organ system - Jillapegu, Margaret Viola; Srinivasulu, Dhishan Sai Kumboju; Sarikonda, Umamaheswara Raju; Ponnaluri, Raghunatha Rao; Tiruveedhula, Jahnavi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adverse drug reactions (ADRs) represent a major public health problem. The overall ADR rate is estimated to be 6.5 and 28% of these are preventable.ADR incidence in Indian population ranges between 1.8-25% with 8% resulting in hospitalization. Hence, the present study was undertaken to study the pattern of reported adverse drug reactions with reference to specific drug class and organ system in a tertiary care hospital. Methods: A cross-sectional retrospective study was carried to analyse the ADRs reported over a period of one year (January-December 2019). Individual case safety reports (ICSRs) of all patients of suspected adverse drug reactions seen in various out-patient departments and admitted in the wards of the hospital were included in the study. The ICSRs were analysed for patient demography, causality, severity and with reference to specific drug class and organ system. Results: Among 382 reported ADRs, 27.2% of the ADRs were reported as serious. The most common therapeutic class of drugs causing ADRs where Antimicrobial agents (36.07%). The skin is the most common affected organ system (25.39%). Conclusions: A coordinated system of identifying the ADRs early in the course of treatment and recognizing the preventable ADRs is required by the health care system. The coordination of prescribing physicians and pharmacovigilance personnel can produce better trend of reporting the ADRs.